POSITIVE IMPACT OF IMPLEMENTING KNOWLEDGE MANAGEMENT ON LECTURER PERFORMANCE DURING THE COVID-19 PANDEMIC - Sirait, Ronnie Togar Mulia; Ginting, Maretta (JURNAL DARMA AGUNG, 2024)
The COVID-19 pandemic has prompted higher education institutions to adapt swiftly to remote teaching environments, highlighting the importance of knowledge management in sustaining lecturer performance. This study investigates the positive impact of implementing knowledge management on lecturer performance during the pandemic. Through qualitative research methods, including in-depth interviews and observations, eight lecturers from various disciplines were interviewed to gather insights. The findings reveal that knowledge management plays a crucial role in enhancing lecturer effectiveness by facilitating strategic planning, talent prioritization, and the integration of technological advancements. Furthermore, knowledge management fosters collaboration, knowledge sharing, and continuous improvement among lecturers, contributing to the resilience and proficiency of higher education institutions amidst the pandemic. Recommendations are made for institutions to fully utilize knowledge management strategies to enhance lecturer performance and maintain competitiveness in the higher education landscape. Further research is suggested to explore the effectiveness of knowledge management in different types of universities and to raise awareness of its significance in achieving institutional success.